Follow up the presence of aflatoxins B1, B2 in wheat, flour and bran (Journal of the College of Basic Education, 2022)
I isolated six genera of mold from wheat grains: Aspergillus,, Rhizapus , Fusarium , Alternaria , Mucor , Penicillium I isolated the threeThe first was isolated from flour while Peniillium, Aspergillus was isolated from bran.The wheat grains used for making flour were contaminated with aflatoxins B1 and B2 in high concentrations.8.12 and 92.99 mg: kg respectively, and decreased as a result of industrialization to become 4.120.17, respectively, with decreasing rates (97.9 and 95.3), respectively. Product storage ledFlour showed a continuous decrease in the concentration of these toxins until they almost disappeared after 95 days of exposure